Tarekat Qadiriyyah Naqsyabandiyyah Suryalaya: Penyebaran dan Pengaruhnya di Aceh - Marzuki Marzuki (Nizham Jurnal Studi Keislaman, 2013)
Tsunami in Aceh in 2004, has made increasingly recognized Aceh in Indonesia and even the world. This opens up opportunities for the inclusion of a wide range of influence on the people of Aceh, including the practice of religion. In 2005, boarding Suryalaya in Tasik Malaya of West Java is one of the boarding school that participated in helping the unfortunate people of Aceh tsunami with Dai and sending volunteers to Aceh. at that moment, the Dai began to introduce the tarekat Qadiriyyah Naqsyabandiyyah in Aceh. The entry of orders Qadiriyyah Naqsyabandiyyah of Pesantren Suryalaya became a new phenomenon in the practice of the Order of Aceh. because of previous orders are popular and practiced by the majority of the people of Aceh are tarekat Naqsyabandiyyah. This study aims to reveal the existence Qadiriyah Naqsyabandiyyah in Aceh, as well as its influence on the practice of tarekat in Aceh. The results showed that this tarekat since coming to Aceh in 2005 still exist and are followed by the different walks of life in Aceh. The tarekat was able to attract people of Aceh from various circles. Tarekat Qadiryyah Naqasyabandiyyah seem attractive and very easy to be carried out, so it continues to grow, and it has a very significant influence on the development of tarekat in Aceh